Hydrogen production and carbon dioxide enrichment from ethanol steam reforming followed by water gas shift reaction. (20th September 2017) - Chen, Chih-Chun; Tseng, Huan-Hsiung; Lin, Yu-Li; Chen, Wei-Hsin
Abstract: Hydrogen production from a two-stage reaction, namely, the ethanol steam reforming (ESR) followed by the water gas shift reaction (WGSR), is experimentally investigated in this study. A Ni/Al2 O3 catalyst and a Fe/Cr2 O3 catalyst are employed to trigger the ESR and WGSR, respectively, and four operating parameters, including the feed liquid flow rate, water-to-carbon (H2 O/C) molar ratio, ESR temperature, and WGSR temperature, are taken into account. To analyze the impact of the operating parameters upon the chemical reactions and maximize the H2 yield from ethanol, the Taguchi method considering the four factors along with three levels is adopted. The results suggest that the influences of the factors on the H2 yield are ranked by H2 O/C ratio > ESR temperature > WGSR temperature > liquid flow rate. In light of the optimal operation suggested by the Taguchi approach, ethanol is completely consumed and the maximum H2 yield is 4.26 mol/(mol C2 H5 OH). This value accounts for around 73% of theoretical H2 yield based on thermodynamic analysis. Meanwhile, the CO2 concentration in the product gas is enriched to 21.77%, whereas the CO one is as low as 0.81%. These evidences reveal that the two-stage reaction can reach the requirement of high H2 yield along with low CO formation, and is conducive to CO2 capture. Graphical abstract: Highlights: Hydrogen production from ethanol steam reforming followed by water gas shift reaction is studied. The Taguchi method is adopted to find the optimal operation for H2 production. The water-to-carbon (H2 O/C) molar ratio plays a key role in determining H2 yield. The maximum H2 yield is 4.26 mol/(mol C2 H5 OH) and CO2 concentration is 21.77%. The two-stage reaction can effectively produce H2 and lower CO formation.